2019
DOI: 10.29309/tpmj/2019.26.06.3593
|View full text |Cite
|
Sign up to set email alerts
|

Needle stick injury reporting among surgeons in tertiary hospitals of Lahore

Abstract: Background: Needle stick injuries have a fairly common incidence in surgical practice exposing surgeons to an array of transmissible diseases. The aim of the study was to assess the prevalence of needle stick injury, and their reporting among surgeons in tertiary hospital setting. Study Design: Cross-sectional study. Setting: Various tertiary care hospital of Lahore. Period: January 2016 through April, 2016. Methods: Our sample size was 935 Surgeons. We determined the prevalence of needle stick injuries, repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…As the current study found that very few of the cases of needle stick injury have been reported due to lack of efficient system of reporting and awareness among doctors about the protective measures and the current findings are consistent with other study in Pakistan, reporting 0.29% prevalence of needle stick injuries among consultants, 24.5% among post-graduate residents and 44.7% among house officers [22]. There is a need of safety awareness programs including safe methods of passing instruments, use of blunt tip needles, double gloves and gowns.…”
Section: Discussionsupporting
confidence: 91%
“…As the current study found that very few of the cases of needle stick injury have been reported due to lack of efficient system of reporting and awareness among doctors about the protective measures and the current findings are consistent with other study in Pakistan, reporting 0.29% prevalence of needle stick injuries among consultants, 24.5% among post-graduate residents and 44.7% among house officers [22]. There is a need of safety awareness programs including safe methods of passing instruments, use of blunt tip needles, double gloves and gowns.…”
Section: Discussionsupporting
confidence: 91%
“…The surgeons practicing in the system are burdened over un-quantified risk exposure. 7 The objectives of the study are to estimate the prevalence of exposure incidents in HCP in OTs; to understand perception about safety culture and to explain the challenges faced by HCP in OTs.…”
Section: Introductionmentioning
confidence: 99%